Railway advertising and murals as an example of graphic design commissioned by Bank Pekao S.A. in the years 1945–1989 - Drozdowski, Adam (Ars inspiratio: Studies dedicated to Professor Eleonora Jedlińska, 2024)
Bank Pekao S.A. is one of the oldest institutions of this type in the country. Already in the interwar period, it decided to use modern forms of advertising, such as: neon lights. After the war, the Bank commissioned designs for promotional materials from the Poland’s most outstanding graphic designers, such as Waldemar Świerzy, Karol Śliwka and Tadeusz Jodłowski. At Pekao’s request, they developed not only multi-colored posters, but also less spectacular forms of advertising, such as leaflets, brochures and packaging for food offered as part of the internal export. In order to reach the widest possible audience, an important role in the history of graphic design on behalf of the institution has been played by forms of advertising appearing in public space, in particular at railway stations and inside the trains, but also as large-format murals placed on the walls of buildings in prominent locations. However, organizing advertising methods in a centrally planned economy was not an easy task. The implementation of the projects used to be hampered by a lack of appropriate materials, as well as logistical difficulties, due to the printing industry’s weak capacity. Nonetheless, in an era associated mainly with the hardships of everyday life and the all-pervading „greyness”, the advertising materials ordered by Pekao, delighted with their interesting forms, expressive colors and high level of workmanship.